Structural Based Screening of Antiandrogen Targeting Activation Function-2 Binding Site - Liu, Yangguang; Wu, Meng; Wang, Tianqi; Xie, Yongli; Cui, Xiangling; He, Liujun; He, Yang; Li, Xiaoyu; Liu, Mingliang; Hu, Laixing; Cen, Shan; Zhou, Jinming (Frontiers in Pharmacology, 2018)
Androgen receptor (AR) plays a critical role in the development and progression of prostate cancer (PCa). Drug resistance mutations at hormone binding pocket would switch currently clinically used antiandrogens from antagonist to agonist of AR. The development of novel antiandrogens to circumvent the mutation based resistance is highly demanded. Herein, through structural analysis of AR structures with ligands binding to the AF2 site, we built a combining pharmacophore model. A silicon screen and the subsequent biological evaluation leads to the discovery of the novel lead compound IMB-A6 that binds to the AF2 site, which is able to inhibit the activity of either wild type and resistance mutanted ARs. Our work demonstrates structure based drug design is an efficient strategy in development of antiandrogen, and provides a new class of small molecule antiandrogen for the development of novel treatment agents of prostate cancer.